Analisis Dhikr sebagai Kesadaran Tauhid dalam Surah Thaha [20] Ayat 14: Perspektif Al-Tafsir Mafatih Al-Ghayb dan Semiotika Karl Buhler - Eva Naria; Piet Hizbullah Khaidir; M. Arromu Harmuzi (Studia Quranika, 2024)
The pronunciation of dhikr in the Qur'an is mentioned 292 times, with various forms of the word derivation (sighat). One form of the word in the form of isim masdar is found in QS. Thaha [20]: 14. This research is a library research with an analysis approach of the Qur'an (interpretation) and philosophy. The method used in this study is the method of philosophical interpretation of Muhammad Fakhr al-Din al-Razi and Karl Buhler's Psycholinguistic Semiotics. The main objective of this study is to determine the relationship between dhikr and tauhid. The researcher describes data about the concept of dhikr in the Qur'an Surah Thaha [20]: 14 perspectives of al-Tafsir Mafatih al-Ghayb and Karl Buhler's Psycholinguistic Semiotics. The results obtained from this study are that dhikr as monotheistic awareness is not enough to be done only with theoretical knowledge. Monotheism that is carried out only with theoretical knowledge will only be informative. Therefore, it is necessary to have an awareness of knowledge and an actual awareness that is affirmative in nature, to achieve true monotheism.